Ethnochemistry: Studying The Food Chemistry In The Making of Kapurung - Imranah, Imranah; Yusaerah, Nur; Wana, Nur; Faradita, Udita (Universitas Pendidikan Mandalika, 2024)
Kapurung is a traditional food from South Sulawesi, especially from Tanah Luwu/Luwu Raya. This food is made from sago (Metroxylon sago) as the basic ingredient which is processed together with various vegetables and meat or fish. The concept of ethnochemistry is used to examine the process of making kapurung through analyzing the natural ingredients used and the chemical changes that occur during processing. The way kapurung is made reflects the local knowledge of the community in managing existing natural resources. The research was conducted to reveal the chemical aspects and fundamental chemical activities contained in the process of making kapurung.This research uses descriptive qualitative research with ethnographic methods, namely observation, interviews, and documentation. Data analysis in this study used source triangulation which was carried out inductively, so that in this study key informants, main informants and supporting informants were determined on each aspect that became the object of research.The results showed that the fundamental chemical activities contained in the kapurung making process are the gelatinization of starch in sago, protein denaturation, fiber degradation and the dissolution of nutrients in vegetables, the Maillard reaction in fried/roasted fish/chicken, and the use of food additives in the kapurung making process.